Moderating Role of Supply Chain Performance in the Relationship Between Inventory Management Practices and Operational Performance of Public Hospitals in Kenya: Evidence from Siaya County (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Kenyan public hospitals face persistent operational performance challenges arising from medicine stock-outs, replenishment delays, and service delivery inefficiencies linked to weaknesses in inventory management and underperforming public healthcare supply chains. This study examined the moderating role of supply chain performance on the relationship between inventory management practices and operational performance of public hospitals in Kenya, using evidence from Siaya County. Inventory management practices were operationalized through Just-in-Time (JIT) replenishment, Inventory Categorization, and Demand Forecasting, while supply chain performance captured supplier responsiveness, delivery reliability, and procurement coordination. The study was anchored on the Resource-Based View and Network Perspective Theory, which explain how internal inventory capabilities and inter-organizational supply chain relationships jointly influence organizational performance. A cross-sectional survey design was adopted. From a target population of 106 hospital personnel, a sample of 84 respondents was selected using the Yamane formula, with stratified proportionate and simple random sampling techniques applied. Primary data were collected using structured questionnaires and interview guides. Reliability was confirmed using Cronbach’s alpha (α ≥ 0.70), and validity was established through expert evaluation. Descriptive statistics summarized the data, while hierarchical regression analysis tested direct and moderating effects. Results revealed that inventory management practices had a positive and statistically significant effect on operational performance (F-statistics (1, 79) was 12.631, p < 0.002). Further, supply chain performance significantly moderated this relationship, such that hospitals with stronger supplier responsiveness and delivery reliability experienced greater operational gains from effective inventory management. The study concludes that improving supply chain performance strengthens the impact of inventory management practices on hospital operational outcomes, including medicine availability, reduced stock-outs, and service delivery efficiency. It recommends that public healthcare systems strengthen supplier integration, procurement coordination, and replenishment reliability to enhance the effectiveness of inventory management and optimize hospital performance.